LNG accident dynamic simulation: Application for hazardous consequence reduction - Sun, Biao; Guo, K. (Elsevier Ltd, 2013)
The evaluation of exclusion (hazard) zones around the LNG stations is essential for risk assessment in LNG industry. In this study, computational fluid dynamics (CFD) simulations have been conducted for the two potential hazards, LNG flammable vapor dispersion and LNG pool fire radiation, respectively, to evaluate the exclusion zones. The spatial and temporal distribution of hazard in complex spill scenario has been taken into account in the CFD model. Experimental data from Falcon and Montoir field tests have been used to validate the simulation results. With the valid CFD model, the mitigation of the vapor dispersion with spray water curtains and the pool fire with high expansion foam were investigated. The spray water curtains were studied as a shield to prevent LNG vapor dispersing, and two types of water spray curtain, flat and cone, were analyzed to show their performance for reduction and minimization of the hazard influencing distance and area. The high expansion foam firefighting process was studied with dynamic simulation of the foam action, and the characteristics of the foam action on the reduction of LNG vaporization rate, vapor cloud and flame size as well as the thermal radiation hazard were analyzed and discussed.